Rehabilitating government : pay and employment reform in Africa (Hong Kong, 1994)
A collection of essays that reflect the complexities of designing civil service pay and employment reforms. This volume documents the nature and extent of prevailing difficulties and examines lessons learned from the implementation of reforms in civil service pay and employment.
Keywords: Africa-Officials and employees-salaries